Research on the Construction and Development of High-Level Sports Teams in Chinese Universities - Ling Wang; Xingdong Zhou (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
To ensure that high-level sports teams in universities develop faster, higher, stronger, and healthier, it is very urgent and urgent to study how to develop high-level sports teams in universities. Using the methods of questionnaire, interview, and case analysis, this paper analyzes the current situation of the development of high-level sports teams in Chinese universities (CUHST), identifies the existing problems, and takes the relatively leading table tennis team of East China University of Science and Technology (ECUST) in Shanghai as an example to explore their solutions to the corresponding problems, to provide reference for the further development of high-level sports teams in other universities. The results showed that the contradiction between learning and training was still the main problem perplexing the construction and development of high-level sports teams in universities. At the same time, the problems of injury problems, low training quality, and less competition times also directly lead to the decline of student athletes' sports levels. The table tennis team of East China University of Science and Technology has taken targeted measures on the above problems and achieved good results. Therefore, to accelerate the construction of high-level sports teams in universities, the key is to grasp the core of the problem, sort out the existing effective methods, and form experience. For government departments, system innovation is needed, and for universities themselves, concepts need to be updated.